Estudio de los problemas de conectividad en los equipos terminales en In.Planet Sucursal Babahoyo - Coello Elizondo, Luis Alberto (2017)
This case study is a product of the analysis that was carried out in order to obtain my third degree in the Degree in Systems Engineering using the Scientific Observation Method, since I worked at the internet provider company and discovered certain inconsistencies and were polished, in order to determine a favorable solution, as far as the research subline was based on Networks and Data Transmission. The internet provider company In.Planet SA with more than 18 years in it, computer market, whose main activity was to provide Cyber ​​Café service in the City of Miracle to see considerable revenues and the labor market feasible in terms of the sale of service of internet, it was growing where it began with a micro-type cyber in the City of Miracle, received a foreign investment where it began to expand in miracle positioning towers to gain more distances and to hoard more clients that investment gave favorable results that cyber became in the present time in a large company. In.planet has more than 5 branches such as the branch Babahoyo who at first had almost no advertising to more than one large poster and the colors that identified it as a branch provider of internet and their customers made references of the service they provided. Currently, the main activity of this company is focused on providing Internet service to different legal natural persons known as SMALL plans, corporate HOME addresses or PREMIUM as large public or private companies, the branch that is located in the city of Babahoyo in the In recent years there has been a strong demand for expansion of personal coverage and availability of user hookups in and out of the city of Babahoyo. users is due to the facilities of payments and to the low costs of the equipments the easy installation and maintenance of the equipment with difference of the conventional wired networks.